Ionic liquids catalyzed lignin liquefaction: mechanistic studies using TPO-MS, FT-IR, RAMAN and 1D, 2D-HSQC/NOSEY NMR - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Green Chemistry, 2016)
Valorization of a profusely available alternate resource, biomass and in particular its 3-D intricate component lignin into low molecular weight aromatic products are used as platform chemicals and fuel additives, and developing a low temperature catalytic process is imperative in preserving atom efficiency. Ionic liquids, due to their unique properties, offer an advantage to develop such methods under milder conditions. Herein, we show use of -SO3H functionalized imidazolium based various recyclable Bronsted acidic ionic liquids (BAILs) in catalytic quantity under ambient pressure at 120 degrees C for depolymerization of lignin (60 000 g mol(-1)) into THF soluble products with high efficiency (78% yield, 95% +/- 5% mass balance). The decoding of this efficiency by 1D and 2D (HSQC/NOSEY) NMR, FT-IR and RAMAN studies exemplify that the -OH group(s) interact with the electron deficient BAIL cation. The mechanistic insights unraveled in this study open a plethora of opportunities to design catalysts for developing efficient processes.